The Effect of Foot Reflexology on the Severity of Labor Pain: a Systematic Review Study - Neda Sharifi; Narjes Bahri (Mashhad University of Medical Sciences, 2019)
Introduction: Although labor pain is a part of labor progression, but uncontrolled pain can be dangerous for both mother and fetus. Reflexology has been reported in some studies as one of the non-pharmacological methods of labor pain relief, but the results of these studies have been contradictory. Therefore, this systematic review was performed with aim to investigate the effects of reflexology on the severity of labor pain. Methods: In this review study, to access relevant articles, the English databases of Google Scholar, Scopus, Pubmed, and Science Direct were searched using the key words of "Pain", "Labor pain", "Reflexology" and "Foot Reflexology", as well as Persian databases including Magiran, SID, and Google Scholar with equal Persian keywords. Also, search was done as a combination of keywords using Bullins from inspection until May 2019. The quality assessment of the included studies was done using of the CONSORT 2017 checklist. Results: Of the 336 studies found from the databases, 7 studies with inclusion criteria were included. The results of the studies showed that foot reflexology during labor reduce the severity of labor pain. Conclusion: Foot reflexology during labor can be effective in reducing the severity of labor pain. Therefore, it is suggested that this low-cost and easy method be used to reduce labor pain.